Road to a New Vision of Arbitration in Public Procurement - Rojas Delgado, Magali Fiorela (2015)
The present article pretends to explain the new framework designed for the regulation for arbitration on public procurements matter, which will begin to operate since the approval of the Regulation for the integral reform for the Public Procurements Peruvian Law. This new vision will allow appreciating the exceptional legal nature that covers arbitration on public procurements, considering transparency and publicity as essential axis to fight corruption, and also the need to ensure specialization on administrative law, arbitration and public procurement on those who resolve disputes on that field.